Why Do People Intend to Report E-Procurement Fraud? In Perspective Theory of Planned Behavior (TPB) - Widiasmara, Anny; Irianto , Gugus; Iqbal , Syaiful; Ghofar , Abdul (Accounting Department,, 2024)
Purpose—This paper aims to discuss the factors that cause individuals to intend to report fraud, especially in the context of procuring goods and services through E-Procurement. Design/methodology/approach — This paper is a literature review that discusses the intention to report fraud by employees in the public sector reporting fraud in public procurement. This review uses the Planned Behavior Theory, which explains the intention to report fraud. Findings—Government agencies' procurement of goods and services is most vulnerable to corruption. Vulnerability: Not only institutions as organizers but also individual employees who have authority in public procurement activities are also vulnerable to allegations of fraud or corruption. Practical implications — This research can also serve as a guideline to assist public sector organizations in designing effective internal control systems to prevent fraud in public procurement processes and practices. Through E-procurement, however, an anti-corruption strategy can only be implemented effectively if it involves all important stakeholders, including government, civil society, non-governmental organizations, the private sector, media, and other key players participating in the public procurement process. Originality/value — Paper type — Literature review